Pemasaran Sosial Berbasis Komunitas pada Satgas Naturalisasi Ciliwung Kota Bogor - Diana Amaliasari; Karina Pramita Ningrum; Feliks Markus Agustin; Amanda Rahmadiani (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
Environmental pollution issues in the Ciliwung River Basin based on latest data from press release of the Ministry of Environment on August 2025 shows that 87.09% of the pollution in the Ciliwung River is dominated by domestic waste, while waste remains an important component of pollution. The Ciliwung River plays an important role for the communities along its banks. Therefore, the Komunitas Peduli Ciliwung (KPC) and the Bogor City Government formed the Ciliwung Naturalization Task Force, which conducts outreach and provides assistance to change the habit of dumping waste into the river. In response to this problem, the Ciliwung Naturalization Task Force was formed to keep the Ciliwung River clean. This community has undertaken several efforts to tackle waste and rehabilitate the ecosystem, including socialization. This study aims to explore how social marketing approaches influence behavioral change among residents, linking it to the Elaboration Likelihood Model. The method used qualitative case study based on in-depth interviews with task force leaders, analyzed thematically and mapped onto marketing components. The findings show that the task force's strategy combines relevant and emotional messages, utilizes media channels such as poster, e-flyers, educational videos, and strengthens the credibility of communicators. The results of this study show that the sustainability of behavior still requires repetition of messages and systematic structural support to ensure that waste sorting practices are consistent. In practical terms this study indicated the need for community-based social marketing designs.